An Unusual Cause of Failure to Ventilate - John T. Denny MD; Sagar S. Mungekar MD; Benjamin R. Landgraf MD; Zoe M. Rocke BS; Valerie A. McRae MD; Christian P. McDonough MD; James T. Tse MD, PhD; Scott J. Mellender MD; Geza K. Kiss MD (SAGE Publishing, 2018)
We report an unusual case of endotracheal tube failure. It was due to a manufacturing defect in the internal white plastic piece that is normally depressed by the luer-lock syringe within the blue pilot balloon. Prior to use, the endotracheal tube was tested and functioned normally. A 64-year-old patient in the intensive care unit with a history of hypertension was being mechanically ventilated after uneventful abdominal surgery. After several hours in the intensive care unit, he was noted to be suddenly no longer receiving adequate tidal volumes from the ventilator. It was found that the cuff on the endotracheal tube was not retaining air when it was filled with air from a syringe. This lead to a large "leak" around the endotracheal tube such that the intended tidal volumes set on the ventilator were not delivered to the patient. The patient was uneventfully reintubated and did well. Subsequent investigation revealed the cause to be a manufacturing defect in the internal white plastic piece that is normally depressed by the luer-lock syringe within the blue pilot balloon. Other mechanisms of cuff failure are reviewed in this case report. This case is an unusual reason for cuff failure. Illustrations supplied alert the reader how to identify the appearance of this manufacturing defect in a pilot balloon. This case illustrates the potential device malfunctions that can develop during a procedure, even when the equipment has been tested and previously functioned well. Even small defects developing in well-engineered products can lead to critical patient care emergencies.